The relationship between parental upbringing and divorce in Saudi Society Utilizing Case Study Approach: A case study in Jeddah province for a sample of divorced men and women - Al-Khazraj, Yahya Turki; Alghamdi, Mohammed Ahmed (Journal of Humanities & Social Sciences, 2024)
The study aimed to find out the relationship between marital parental upbringing and divorce in Saudi society. The study was applied to a sample of divorced men and women in Jeddah Governorate using the case study approach. Data was collected using an interview tool. The research population consisted of (30) cases, and the study population included cases that fell under It was called (divorced, divorced) during the period of conducting the study, and the most important results of the study revealed that the number of cases in which divorce occurred due to poor marital upbringing by parents amounted to (40%) of the study sample, and this was represented by a lack of honesty, respect, and concern for the concept of a good reputation. . The results of the study also revealed that there is a relationship between weak emotional marital upbringing by parents and the occurrence of divorce, and this weakness was evident in the lack of prevalence of emotional expressions. The results of the study also revealed that weak marital socialization has an impact on the occurrence of divorce, represented by a low level of dialogue between parents and a lack of communication with relatives. One of the most prominent recommendations of the study is to provide a therapeutic vision related to the emotional and sexual aspects that is compatible with the specificity of Saudi society so that society does not resist it, and that it is derived from the Holy Qur’an and the purified Sunnah of the Prophet.